Soyfood and isoflavone intake and risk of type 2 diabetes in Vietnamese adults - Nguyen, C T; Pham, N M; Do, V V; Binns, C W; Hoang, V M; Dang, D A; Lee, A H (European journal of clinical nutrition, 2017)
Background/Objectives: Animal studies have demonstrated that soy isoflavones exert antidiabetic effects. However, evidence regarding the association between soyfood intake, a unique source of isoflavones, and type 2 diabetes remains inconclusive. This study assessed the relationship between habitual intakes of soyfoods and major isoflavones and risk of type 2 diabetes in Vietnamese adults. Subjects/Methods: A hospital-based case-control study was conducted in Vietnam during 2013–2015. A total of 599 newly diagnosed diabetic cases (age 40–65 years) and 599 hospital-based controls, frequency matched by age and sex, were recruited in Hanoi, capital city of Vietnam. Information on frequency and quantity of soyfood and isoflavone intake, together with demographics, habitual diet and lifestyle characteristics, was obtained from direct interviews using a validated and reliable questionnaire. Unconditional logistic regression analyses were performed to examine the association between soy variables and type 2 diabetes risk. Results: Higher intake of total soyfoods was significantly associated with a lower risk of type 2 diabetes; the adjusted odds ratio (OR) for the highest versus the lowest intake was 0.31 (95% confidence interval (CI): 0.21–0.46; P <0.001). An inverse dose–response relationship of similar magnitude was also observed for total isoflavone intake (OR: 0.35; 95% CI: 0.24 to 0.49; P <0.001). In addition, inverse associations of specific soyfoods (soy milk, tofu and mung bean sprout) and major isoflavones (daidzein, genistein and glycitein) with the type 2 diabetes risk were evident. Conclusions: Soyfood and isoflavone intake was associated with a lower type 2 diabetes risk in Vietnamese adults.